Carbon Dioxide Electroreduction: Orbital Interactions in Bi‐Sn Bimetallic Electrocatalysts for Highly Selective Electrochemical CO2 Reduction toward Formate Production (Adv. Energy Mater. 31/2018). Issue 31 (5th November 2018) - Wen, Guobin; Lee, Dong Un; Ren, Bohua; Hassan, Fathy M.; Jiang, Gaopeng; Cano, Zachary P.; Gostick, Jeff; Croiset, Eric; Bai, Zhengyu; Yang, Lin; Chen, Zhongwei
Abstract : In article number1802427, Zhengyu Bai, Zhongwei Chen, and co‐workers reveal orbital interactions of Bi‐Sn nanostructures, leading to the electrocatalytic conversion of CO2 to formate with high selectivity, activity, and durability. This is attributed to the electronic states of Sn upshifting away from the Fermi level due to the coupling with Bi, making the HCOO* intermediate adsorb more favorably on Bi‐Sn than on pure Sn surfaces. This study provides sub‐atomic level insights into bimetallic catalyst development for highly selective CO2 reduction.